Evaluating the Effect of Different Mouthwashes on the Titanium and Nickel Ions Released from Ordinary and Blue NiTi Archwires (An In-vitro Study) - Noor Nourie Abbass Abdullah (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objectives: This studywas carried out to evaluate the effect of alcohol present in mouthwash on the Ni and Ti ions release from ordinary andblue NiTiarchwire.Materials and Methods: Sixty specimens of 2cm length from 0.017×0.025 inch maxillary Flexy and Blue Flexy NiTi archwire (30 per each archwires) were immersed in 15 ml. distilled water, alcoholic and alcohol-free Corsodyl mouthwashes (10 per immersing media for each archwire) for one and half hour. After that, Ni and Ti ions released in mouthwashes and distilled waterwere measured using atomic absorption spectrophotometer. Unpaired sample t-test and one way ANOVA test were used for comparison between the archwire types and among different immersion media.Results: Regarding Ni ion, the release of this ion washigher significantly in distilled water followed by alcohol-free Chlorhexidine while the least amount released in alcoholic Chlorhexidine. For Ti ion, the higher amount of Ti ion was released significantly from alcoholic Chlorhexidine followed by alcoholfree Chlorhexidine and the least amount was released in distilled waterin both types of archwires.Both ions were released significantly more from conventional NiTi archwire in all mouthwashes.Conclusions: Ions released from the tested archwires appear to be low with blue NiTi archwire. Ni ion was released more with alcohol-free mouthwash and just the opposite forTiion.